Caenorhabditis elegans stress related gene responses to selected pesticides - Antoniou-Kourounioti, Melissa (2010)
Pesticides are used widely and more than 2 million tons are released in the environment annually (data for 2000-2001, Kiely 2004). Details of their toxicity towards non-target organisms, are not complete for many of these pesticides and serious environmental issues have previously arisen as a result (e.g. effects of DDT on reproduction of wild birds). Unfavourable conditions, including the presence of toxicants, can induce the stress response pathways through which an organism attempts to metabolise the harmful chemicals or counter their effects. The stress response network contains a number of gene pathways controlled by transcriptional regulators which control expression of genes in one or several groups. In their attempt to counter stress, stress-response genes act in an interactive manner and should therefore be studied together as a network, rather than individually. This study examines the effect of a number of commonly used pesticides on C. elegans, a non-target organism. We focus on stress-response gene expression patterns and in some cases perform assays for physiological effects. We also present supplementary qPCR experiments to confirm previous results on the effect of dichlorvos on C. elegans gene expression. Our results show that some tested pesticides are not toxic to the nematode, whereas rotenone proves highly toxic and chlorpyriphos, endosulfan, DDT and carbendazim are moderately toxic with DDT showing significant inhibition of feeding as well. Our data partly confirm the gene array results previously obtained for dichlorvos. Our study provides information on how a number of pesticides affect stress-response gene expression. Together with previous data on the effect of heavy metals and parallel data from Drosophila, these findings will inform the development of a dynamic mathematical model of the stress-response network (SRN).